1978
DOI: 10.1002/j.1551-8833.1978.tb04164.x
|View full text |Cite
|
Sign up to set email alerts
|

Constant‐Rate and Constant‐Pressure Filtration Look Similar—But Are They?

Abstract: Work on correlating constant‐rate and constant‐pressure filtration has been inconclusive. The author shows that correlation is not possible with current technology and explains why.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1979
1979
1999
1999

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 5 publications
0
2
0
Order By: Relevance
“…In Figure 9 with the higher compressibility talc system significant differences between theoretical predictions and experimental data are typically seen. Several researchers [15][16][17], including the author [18], have questioned the philosophy of combining filtration data obtained over different pressure/flow regimes as there are inherent differences between cakes formed under conditions of constant and variable pressure. When compressibility is present in a forming cake, the rate of change in the pressure gradient across the cake affects the manner in which the particles in the cake are arranged, and this in turn influences both cake resistance and cake porosity.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In Figure 9 with the higher compressibility talc system significant differences between theoretical predictions and experimental data are typically seen. Several researchers [15][16][17], including the author [18], have questioned the philosophy of combining filtration data obtained over different pressure/flow regimes as there are inherent differences between cakes formed under conditions of constant and variable pressure. When compressibility is present in a forming cake, the rate of change in the pressure gradient across the cake affects the manner in which the particles in the cake are arranged, and this in turn influences both cake resistance and cake porosity.…”
Section: Discussionmentioning
confidence: 99%
“…Here, it is perhaps more normal to transport suspensions into filter chambers using either positive displacement or centrifugal pumps and perform filtrations according to the pressure and flow characteristics of the pumping device. A few researchers have suggested that data obtained at constant pressure may not correctly predict filtrations over other pressure regimes and some have attempted difficult laboratory experiments in order to assess performance at constant flow/variable pressure or variable pressure/variable flow [12][13][14][15][16][17]. Due to experimental constraints only limited progress has previously been possible and it is difficult to resolve the inherent problems of more conventional apparatus/methods, such as particle breakage and surface modification by pumps, with confidence.…”
Section: Introductionmentioning
confidence: 99%